The Encheiridion of Epictetus and its three Christian adaptations - Epictetus. (Philosophia Antiqua, 1999)
Epictetus' Encheiridion , which was composed by his pupil Arrian with the purpose of giving a comprehensive account of Epictetus' thought, has been transmitted in many sources. Besides the rich direct tradition there are three Christian adaptations, a voluminous commentary by the sixth-century philosopher Simplicius, as well as the indirect tradition. The most recent critical edition is the editio maior by Johannes Schweighäuser (1798), which does not meet the requirements of modern philology. In the first part of this book there is a full account of the transmission of Epictetus' Encheiridion and the three Christian adaptations, based on all extant manuscripts. The second part of the book contains critical editions of the four texts; for the Christian Encheiridion of Vaticanus graecus 2231 this is the editio princeps .